Dynamic high-resolution ultrasound of the shoulder: How we do it. Issue 2 (February 2015) - Corazza, Angelo; Orlandi, Davide; Fabbro, Emanuele; Ferrero, Giulio; Messina, Carmelo; Sartoris, Riccardo; Perugin Bernardi, Silvia; Arcidiacono, Alice; Silvestri, Enzo; Sconfienza, Luca Maria
Highlights: This paper shows how to apply US technique to image soft tissues around the shoulder. Readers will learn to recognize normal US anatomy of tendons of the shoulder. Readers will learn to apply dynamic maneuvers to improve rotator cuff visibility. Abstract: Ultrasonography (US) is an established and well-accepted modality that can be used to evaluate articular and peri-articular structures around the shoulder. US has been proven to be useful in a wide range of rotator cuff diseases (tendon tears, tendinosis, and bursitis) as well as non-rotator cuff abnormalities (instability problems, synovial joint diseases, and nerve entrapment syndromes). Diagnostic accuracy of shoulder US when evaluating rotator cuff tears can reach 91–100% for partial and full thickness tears detection, respectively, having been reported to be as accurate as magnetic resonance imaging in experienced hands. US is cheap, readily available, capable to provide high-resolution images, and does not use ionizing radiations. In addition, US is the only imaging modality that allows performing dynamic evaluation of musculoskeletal structures, that may help to further increase diagnostic performance. In this setting, a standardized imaging protocol is essential for an exhaustive and efficient examination, also helping reducing the intrinsic dependence from operators of US. Furthermore, knowledge of pitfalls that can be encountered when examining the shoulder may help to avoid erroneous images interpretation. In this article we use detailed anatomic schemes and high-resolution US images to describe the normal US anatomy of soft tissues, articular, and para-articular structures located in and around the shoulder. Short video clips emphasizing the crucial role of dynamic maneuvers and dynamic real-time US examination of these structures are included as supplementary material.